Descriptions of two new species of Armatoplana (Polycladida: Stylochoplanidae) from the coasts of Japan, with their phylogenetic positions in Leptoplanoidea - Oya, Yuki; Tsuyuki, Aoi; Kajihara, Hiroshi (Zootaxa, 2022)
We describe two new species of Armatoplana Faubel, 1983, namely, A. albomaculata sp. nov. and A. kaburakii sp. nov., from Japan. This is the first record of the genus from the West Pacific. Armatoplana albomaculata sp. nov. has the following characteristics: i) no nuchal tentacles; ii) white spots on the dorsal surface of the body; iii) an elongated oval prostatic vesicle directing posteriorly but curving dorsally in the distal part; iv) a long, curved penis stylet; and v) a small, oval Lang’s vesicle without accessory vesicles. Armatoplana kaburakii sp. nov. is distinguished from other congeners by having i) no nuchal tentacles; ii) a large, elongated Lang’s vesicle without accessory vesicles; and iii) gonopores opening closely to each other. We propose to re-circumscribe Armatoplana so that it would not become a junior synonym of Candimboides Prudhoe, 1982 and Phylloplana Laidlaw, 1903. We provide partial sequences of the mitochondrial cytochrome c oxidase subunit I (COI) gene as DNA barcodes for the two new species. Our phylogenetic analyses based on concatenated sequences of the 16S, 18S, and 28S ribosomal DNA and COI revealed that A. albomaculata sp. nov. and A. kaburakii sp. nov. were sister taxa; however, they did not form a monophyletic clade with Armatoplana divae (Marcus, 1947) and Armatoplana leptalea (Marcus, 1947).